PEMIKIRAN POLITIK ISLAM PADA MASA PEMERINTAHAN DINASTI ABBASIYAH - Nurlaelah Abbas (Jurnal Dakwah Tabligh, 2016)
This study discusses about the background of a transition of Umaiyah dynasty to Abbasiyah dynasty, The project role of Abbsiyah khalifah to get eventually the highest achievement in its time, and the things make Abbasiyah dynasty is ruined. This study is aimed to know the background of a transition from Umaiyah dynasty to Abbasiyah dynasty, to ascertain the project role of Abbsiyah khalifah to get the highest achievement in its time at last, and to find out the things make Abbasiyah dynasty is falled apart. The type of the research is a descriptive qualitative done through a documentation study. Data collected through documentation, using library research. Sources of data obtained through primary data and secondary data. The data obtained are then processed with an inductive method by clarifying the formal object of the research from general to specific.The outcome of this study points out that The transition of Bani Umayyah to Abbsiyah dynasty takes place as political movements when Bani Hasyim demands the Islam leader must be in their hands which is due to they are the closed prophet Muhammad’s relatives. The era of Daulah Abbasiyah is the golden age of Islam where the sovereignity of Islam is about in the top either in wealth, advancement, or authority. In the era of Abbasiyah, there is a lesson that can be learned which is Islam people do not to be distracted by the world power because that thing and luxury living cause a part from Allah swt’s teachings.